Immunodominance of Epitopes and Protective Efficacy of HI Antigen Are Differentially Altered Using Different Adjuvants in a Mouse Model of Staphylococcus aureus Bacteremia - Chen, Zhifu; Gou, Qiang; Xiong, Qingshan; Duan, Lianli; Yuan, Yue; Zhu, Jiang; Zou, Jintao; Chen, Longlong; Jing, Haiming; Zhang, Xiaoli; Luo, Ping; Zeng, Hao; et al. (Frontiers in Immunology, 2021)
HI, a fusion protein that consists of the alpha-toxin (Hla) and the N2 domain of iron surface determinant B (IsdB), is one of the antigens in the previously reported S. aureus vaccine rFSAV and has already entered phase II clinical trials. Previous studies revealed that HI is highly immunogenic in both mice and healthy volunteers, and the humoral immune response plays key roles in HI-mediated protection. In this study, we further investigated the protective efficacy of immunization with HI plus four different adjuvants in a mouse bacteremia model. Results showed that HI-mediated protection was altered in response to different adjuvants. Using antisera from immunized mice, we identified seven B-cell immunodominant epitopes on Hla and IsdB, including 6 novel epitopes (Hla1-18, Hla84-101, Hla186-203, IsdB342-359, IsdB366-383, and IsdB384-401). The immunodominance of B-cell epitopes, total IgG titers and the levels of IFN-γ and IL-17A from mice immunized with HI plus different adjuvants were different from each other, which may explain the difference in protective immunity observed in each immunized group. Thus, our results indicate that adjuvants largely affected the immunodominance of epitopes and the protective efficacy of HI, which may guide further adjuvant screening for vaccine development and optimization.